Oroxylin A inhibits H2O2-induced oxidative stress in PC12 cells. Issue 11 (3rd June 2017) - Han, Qinghe; Wang, Haiyu; Xiao, Chong; Fu, Ben-Dong; Du, Chong-Tao
Abstract: Oroxylin A, a natural flavonoid isolated from Scutellaria baicalensis, has been reported to have anti-inflammatory and antioxidant effects. However, suppression of oxidative stress and neuroapoptosis by oroxylin A is largely uninvestigated. To investigate the protective effects of oroxylin A, PC12 cells were exposed to oroxylin A and hydrogen peroxide solutions and measured. Oroxylin A signiﬁcantly reduced the levels of intracellular calcium and reactive oxygen species and increased the levels of CAT and Mn/SOD. Oroxylin A also inhibited the activation of caspase-3. These results suggest that treatment of PC12 cells with oroxylin A inhibits H2 O2 -induced oxidative stress. Abstract :